Diagnoses and prescriptions of antidepressants in suicides: Register findings from the Friuli Venezia Giulia Region, Italy, 2002–2008. (2nd April 2016) - Castelpietra, Giulio; Bovenzi, Massimo; Clagnan, Elena; Barbone, Fabio; Balestrieri, Matteo; Isacsson, Göran
Abstract: Objective : To explore to what extent and under which diagnoses individuals who committed suicide had received psychiatric in-patient care, and how many had previously committed non-lethal self-harm. To investigate the antidepressant treatment received by these individuals.Methods : Case–control study based on a health register.Results : Psychiatric hospitalisation was found in 31.2% of the cases and 2.3% of the controls, and was a strong predictor for suicide with an odds ratio (OR) = 19.5. This did not differ significantly between diagnostic categories (except anxiety disorders with OR = 5.3). Non-lethal self-harm in the study period was committed by 14.3% of the cases and 0.14% of the controls, and was twice as common in female cases than in male cases. Previous self-harm was a very strong independent predictor for suicide with OR = 53.1 when a single episode of self-harm had occurred, and OR = 98.0 for repeated episodes (adjusted for age, gender and hospitalisation). Only 16.1% of the cases were currently on antidepressant medication at the time of suicide.Conclusions : Few of the suicides had previously been psychiatric in-patients. Even fewer had current prescriptions for antidepressants. This suggests that better diagnosis and treatment of psychiatric patients is an important suicide preventive intervention.